2020
DOI: 10.3389/fmicb.2020.00858
|View full text |Cite
|
Sign up to set email alerts
|

Cannabigerol Prevents Quorum Sensing and Biofilm Formation of Vibrio harveyi

Abstract: Cannabigerol (CBG) is a non-psychoactive cannabinoid naturally present in trace amounts in the Cannabis plant. So far, CBG has been shown to exert diverse activities in eukaryotes. However, much less is known about its effects on prokaryotes. In this study, we investigated the potential role of CBG as an anti-biofilm and anti-quorum sensing agent against Vibrio harveyi. Quorum sensing (QS) is a cell-to-cell communication system among bacteria that involves small signaling molecules called autoinducers, enablin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 41 publications
2
36
0
Order By: Relevance
“…Vasudevan et al [32] found that CBG infused mouthwash products showed similar bactericidal efficacy as that of chlorhexidine 0.2%, while Stahl et al [31] found that cannabinoids were more effective in reducing the bacterial colony count in dental plaques compared with the well-established synthetic oral care products such as Oral B and Colgate. We have demonstrated that CBG has an anti-quorum sensing effect against Vibrio harveyi [33]. Furthermore, we have shown that CBG exerts anti-bacterial effects towards planktonic S. mutans [34].…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Vasudevan et al [32] found that CBG infused mouthwash products showed similar bactericidal efficacy as that of chlorhexidine 0.2%, while Stahl et al [31] found that cannabinoids were more effective in reducing the bacterial colony count in dental plaques compared with the well-established synthetic oral care products such as Oral B and Colgate. We have demonstrated that CBG has an anti-quorum sensing effect against Vibrio harveyi [33]. Furthermore, we have shown that CBG exerts anti-bacterial effects towards planktonic S. mutans [34].…”
Section: Introductionmentioning
confidence: 76%
“…RNA extraction was performed as previously described [33] with slight modifications. An overnight culture of S. mutans (OD 600nm~1 ) was diluted 1:10 in BHI containing 2% sucrose and the biofilms were allowed to form in the absence or presence of CBG (2.5 µg/mL) or respective ethanol concentrations (0.025%) by incubating the bacteria at 37 • C in 95% air/5% CO 2 for 24 h. At the end of incubation, the biofilms were washed twice with PBS and soaked in 2 mL of RNA Protect (Qiagen, Hilden, Germany) for 5 min at room temperature, and the RNA isolation was performed using the RNeasy MINI kit (Qiagen) including on-column DNase digestion according to the manufacturer's instructions.…”
Section: Rna Extractionmentioning
confidence: 99%
“…Farha et al (2020) demonstrated an anti-bacterial activity of CBG against methicillin-resistant S. aureus (MRSA). We have previously shown that CBG did not affect the growth of the gram-negative Vibrio harveyi, but rather interfered with the quorum sensing system (Aqawi et al, 2020). Here we have studied the antibacterial activity of CBG against planktonic growing S. mutans.…”
Section: Introductionmentioning
confidence: 94%
“…CBD was shown to have potent anti-bacterial activity against methicillin-resistant Staphylococcus aureus (MRSA) and Streptococcus isolates with MICs in the range of 1–5 μg/mL [ 19 , 20 , 22 ]. Its related cannabigerol (CBG) interfered with quorum sensing (QS) in Vibrio harveyi with no detectable minimal inhibitory concentration (MIC) [ 23 ]. Pharmacological components of the endocannabinoid system include endocannabinoids (EC), enzymes that synthesize and degrade the EC, and cannabinoid receptors (CB).…”
Section: Introductionmentioning
confidence: 99%